Manajemen Komunikasi Pengelola Zakat Melalui Strategi Human Resources Development - Lina Yulianti (Tadbir: Jurnal Manajemen Dakwah, 2018)
This study aims to analyze the communication management process of UPZ MD managers in terms of the implementation of the Human Resources Development (HRD) strategy. Communication management is both verbal and non-verbal which includes aspects of informing, persuading and collaborating. This research is a descriptive qualitative research. Where this study seeks to analyze the application of communication management through HRD strategies. Data collection is done through interviews and observations. The interview involved key informants from the Da'wah Management Department, permanent lecturers appointed as managers and students as UPZ technical implementers. The results showed that the management of UPZ MD's zakat management was done both verbally and non-verbally. Verbal communication in oral form for example during routine meetings, while in written form for example through the preparation of reports, SOPs, and suggestion sheets. Non-verbal communication is carried out at the time of service to users which is manifested in the form of work principles stated in the SOP and UPZ MD excellent service notice. The implementation of UPZ MD's Human Resources Development (HRD) strategy consists of three aspects, namely the informing aspect (for example, regular meetings, FGD Management, Seminars and Workshops); persuading (UPZ brand image socialization through direct and digital communication media and preparation of the UPZ MD program); and collaborating (in the form of division of labor as evidenced by the UPZ Management SOP and Organizational Structure).